2019
DOI: 10.1038/s41598-019-47112-9
|View full text |Cite|
|
Sign up to set email alerts
|

Parvalbumin expression in oligodendrocyte-like CG4 cells causes a reduction in mitochondrial volume, attenuation in reactive oxygen species production and a decrease in cell processes’ length and branching

Abstract: Forebrain glial cells - ependymal cells and astrocytes -acquire upon injury- a “reactive” phenotype associated with parvalbumin (PV) upregulation. Since free radicals, e.g. reactive oxygen species (ROS) play a role in the pathogenesis of multiple sclerosis, and that PV-upregulation in glial cells is inversely correlated with the level of oxidative stress, we hypothesized that PV-upregulation might also protect oligodendrocytes by decreasing ROS production. Lentiviral transduction techniques allowed for PV over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 69 publications
2
12
0
Order By: Relevance
“…In distinct Pvalb neuron populations in adult PV−/− mice, the mitochondrial volume is augmented and the relative increase strongly correlates with the PV concentration prevailing in the various WT Pvalb neuron subpopulations in the different brain regions, i.e., the higher the concentration of PV, the higher the PV loss-induced increase in mitochondria volume ( Janickova et al, 2020 ). Interestingly, both in CG4 cells and more relevant in PV−/− Pvalb neurons, the increase in mitochondria volume and dendritic mitochondria length is associated with increased branching and length of dendrites ( Lichvarova et al, 2019 ; Janickova et al, 2020 ), in full agreement with the reported increase in genes of module cM1 (‘morphogenesis of branching structures’) in three ASD and schizophrenia mouse models ( Gordon et al, 2019 ). Thus, we set out to investigate the timeline of events caused by the absence of PV.…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…In distinct Pvalb neuron populations in adult PV−/− mice, the mitochondrial volume is augmented and the relative increase strongly correlates with the PV concentration prevailing in the various WT Pvalb neuron subpopulations in the different brain regions, i.e., the higher the concentration of PV, the higher the PV loss-induced increase in mitochondria volume ( Janickova et al, 2020 ). Interestingly, both in CG4 cells and more relevant in PV−/− Pvalb neurons, the increase in mitochondria volume and dendritic mitochondria length is associated with increased branching and length of dendrites ( Lichvarova et al, 2019 ; Janickova et al, 2020 ), in full agreement with the reported increase in genes of module cM1 (‘morphogenesis of branching structures’) in three ASD and schizophrenia mouse models ( Gordon et al, 2019 ). Thus, we set out to investigate the timeline of events caused by the absence of PV.…”
Section: Introductionsupporting
confidence: 78%
“…The volume of the cytoplasm, nuclei and mitochondria were calculated for each neuron using the same parameter and algorithm settings. Statistical analyses were performed using the ‘Imaris Measurement Pro’ module as described previously ( Lichvarova et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…This specific potassium channel subunit composition is almost exclusively expressed within PV neurons and changes when the level of PV decreases [50]. PV levels are also inversely related to cell and mitochondria volume and reactive oxygen species (ROS) production [52][53][54][55], suggesting that the conditioned effects of cocaine-associated memory reactivation could decrease PV through ROS production. Additionally, GAD 67 levels are correlated with NMDAR subunit composition [56].…”
Section: Discussionmentioning
confidence: 99%
“…6A, B and 7A, B. All movie files are available in the ZENODO repository https ://doi.org/10.5281/zenod o.39072 89 1 . The individual frames from which the representative cells were taken are marked and annotated in the "Supporting Information" (.pdf) file available in the same repository.…”
mentioning
confidence: 99%
“…1A, B, G, and H could not be identified. A revised version of Figure 1 appears below, with the corresponding movies, which are available in the ZENODO repository https://doi.org/10.5281/zenodo.3907289 1 , referenced in the figure legend.
Figure 1 CG4 cells display an OPCs-like morphology in the undifferentiated state ( A ) and oligodendrocyte-like phenotype in the differentiated state ( B ).
…”
mentioning
confidence: 99%